Performance Analysis of Selective Mapping in Underwater Acoustic Orthogonal Frequency Division Multiplexing Communication System - Raza, W.; Ma, X.; Ali, A.; Ali, A.; Raza, A.; Shaikh, S. (Engineering, Technology & Applied Science Research, 2021)
Under-Water Acoustic (UWA) communication networks are commonly formed by associating various independent UWA vehicles and transceivers connected to the bottom of the sea with battery-operated power modems. Orthogonal Frequency Division Multiplexing (OFDM) is one of the most vital innovations for UWA communications, having improved data rates and the ability to transform fading channels into flat fading. Moreover, OFDM is more robust on Inter-Symbol and Inter-Carrier Interferences (ISI and ICI respectively). However, OFDM technology suffers from a high Peak to Average Power Ratio (PAPR), resulting in nonlinear distortions and higher Bit Error Rates (BERs). Saving power of battery deployed modems is an important necessity for sustainable underwater communications. This paper studies PAPR in UWA OFDM communications, employing Selective Mapping (SLM) as a tool to mitigate PAPR. The proposed SLM with the oversampling factor method proves to be less complex and more efficient. Simulation results indicate that SLM is a promising PAPR reduction method for UWA OFDM communications reducing BER.